2022
DOI: 10.9745/ghsp-d-21-00237
|View full text |Cite
|
Sign up to set email alerts
|

Role of Information Sources in Vaccination Uptake: Insights From a Cross-Sectional Household Survey in Sierra Leone, 2019

Abstract: Exposure to vaccination information from faith leaders and health facilities was associated with increased likelihood of vaccination uptake. nThe significant association between exposure to a greater number of immunization information sources and increased likelihood of vaccination uptake reinforces the need for multiple sources to provide consistent and accurate immunization information to facilitate positive vaccination behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…In Sierra Leone, where 77% of the population is Muslim and 22% is Christian, religious leaders have long been involved in mobilising communities and raising awareness on childhood immunisation [ 44 , 45 ]. This approach has been supported by findings from a previous study in Sierra Leone that observed a higher immunisation confidence and uptake among those who received related information from faith leaders [ 46 ]. The findings of the present survey highlight the continued call for involving religious and other influential community leaders in health interventions to promote immunisation uptake.…”
Section: Discussionsupporting
confidence: 58%
“…In Sierra Leone, where 77% of the population is Muslim and 22% is Christian, religious leaders have long been involved in mobilising communities and raising awareness on childhood immunisation [ 44 , 45 ]. This approach has been supported by findings from a previous study in Sierra Leone that observed a higher immunisation confidence and uptake among those who received related information from faith leaders [ 46 ]. The findings of the present survey highlight the continued call for involving religious and other influential community leaders in health interventions to promote immunisation uptake.…”
Section: Discussionsupporting
confidence: 58%
“…Participants with one (p-value < 0.001), or two to three (p-value = 0.032) sources of information on COVID-19 vaccines were less likely to take vaccines as compared to participants with more than three sources of information on COVID-19 vaccine. Comparably, an analysis by Kulkarni et al [22] revealed that increased access to multiple sources of information was linked to high rates of vaccine uptake thereby suggesting that acquiring information from varied sources can potentially impact vaccination behaviours and further affecting vaccine uptake rates.…”
Section: Resultsmentioning
confidence: 99%
“…18 In Sierra Leone, vaccine confidence was highest among those who received immunization information from faith leaders. 19 Constructs of the Health Belief Model (HBM) are beneficial in understanding, analyzing, and predicting the acceptance of health-promoting behaviors like vaccinations. 20 The HBM is a value expectancy theory postulating that an individual's desire to prevent an illness (value) and one's belief that a specific health action available would prevent or ameliorate illness (expectancy) is predictive of specific health behaviors.…”
Section: Introductionmentioning
confidence: 99%